ANALISIS SUSTAINABLE VALUE STREAM MAPPING UNTUK PENINGKATAN KEBERLANJUTAN DAN EFISIENSI PROSES PRODUKSI TAHU - Anting Wulandari; Evi Febianti (Jurnal Agroindustri Pangan, 2026)
UMKM Tahu X is a micro-enterprise that still relies on traditional production systems and faces various problems in economic, environmental, and social aspects. This study aims to evaluate sustainability efficiency, identify waste-causing indicators, analyze root causes, and provide improvement recommendations. The method used is Sustainable Value Stream Mapping (Sus-VSM) through observation, time measurement, data collection on energy and water consumption, and social questionnaires. The results show that major waste occurs in energy consumption, physical workload, and work environment temperature. The causes include inefficient use of firewood, manual work processes, and poor ventilation. Improvements were made using the 5W+1H method, resulting in a decrease in energy consumption from 0.233 kWh/kg to 0.166 kWh/kg, physical workload score from 22.068 to 18, and production area temperature from 31.8°C to 27°C. These findings indicate that the implementation of the Sus-VSM approach can enhance the efficiency and sustainability of the production process in Tahu X.